The Effect of Transformational Leadership, Work Environment, and Compensation on Employee Job Satisfaction - Prayuda, Rafie (Journal of Industrial Engineering & Management Research, 2019)
The purpose of this study was to determine the effect of transformational leadership on employee job satisfaction. The influence of the work environment on employee job satisfaction. The effect of compensation on employee job satisfaction. The effect of transformational leadership, work environment, and compensation on employee job satisfaction. This research is a type of quantitative research. The sampling technique in this research is purposive sampling technique. The number of samples in this study were 230 employees. Data collection techniques in this study using a questionnaire. The data analysis methods used in this research are validity test, reliability test, descriptive test, classical assumption test, and multiple linear regression test. The data analysis was conducted to identify the independent variables that affect the dependent variable. The results showed that transformational leadership had no effect on employee job satisfaction. The work environment has an effect on employee job satisfaction. Compensation has an effect on employee job satisfaction. Transformational leadership, work environment, and compensation simultaneously have a significant positive effect on employee job satisfaction.